Pulverized coal particle ignition in a combustion environment with a reducing-to-oxidizing transition. Issue 3 (June 2019) - Adeosun, Adewale; Xiao, Zhenghang; Gopan, Akshay; Yang, Zhiwei; Wang, Xuebin; Li, Tianxiang; Yao, Qiang; Axelbaum, Richard L.
Abstract: A reducing-to-oxidizing (RO) environment is characteristic of what a coal particle experiences in the near-burner region of pulverized coal (pc) furnaces. The RO environment can influence early-stage coal combustion processes such as ignition, aerosol formation, and char burnout. However, fundamental studies have focused on either oxidizing conditions (mimicking the post-flame region) or reducing conditions (mimicking the devolatilization region). The effect of this RO environment on early-stage coal combustion has, until now, not been considered. Here, the role of this reducing-to-oxidizing environment on single-particle ignition is evaluated. Powder River Basin (PRB) sub-bituminous coal was used, with a particle size of 125–149 μm and two nominal gas temperatures of 1300 K and 1800 K. The experimental findings for purely-oxidizing conditions with 20 vol% oxygen are compared with those of reducing-to-oxidizing environment. Single particles were tracked using high speed, high resolution videography. Emission intensities of the particles were used to evaluate the prevailing ignition modes, and to determine the characteristic ignition and induction times in both oxidizing and reducing-to-oxidizing environments. Experimental findings show that homogeneous-to-heterogeneous mode of ignition is prevalent for purely oxidizing conditions for both nominal gas temperatures of 1300 K and 1800 K. However, hetero-homogeneous ignition is favored in reducing-to-oxidizing environment at 1800 K and heterogeneous ignition at 1300 K gas flame temperature. The reducing-to-oxidizing environment leads to longer ignition delay times of about 20% and 40% on average for 1300 K and 1800 K nominal gas temperatures respectively but shorter induction times than those of oxidizing condition. The results show that ignition behavior in a reducing-to-oxidizing post-flame environments can be quite different from those in oxidizing environments. Highlights: Effects of reducing-to-oxidizing environments on ignition behavior of isolated coal particles are identified and compared to oxidizing environments. Hetero-homogeneous ignition is favored in reducing-to-oxidizing environments at 1800 K and heterogeneous ignition at 1300 K gas temperature. Homogeneous-to-heterogeneous ignition is prevalent for oxidizing environments. The reducing-to-oxidizing environment leads to longer ignition delays but shorter induction times than those of oxidizing environments.